2019
DOI: 10.1111/cdev.13320
|View full text |Cite
|
Sign up to set email alerts
|

Minds Under Siege: Cognitive Signatures of Poverty and Trauma in Refugee and Non‐Refugee Adolescents

Abstract: The impacts of war and displacement on executive function (EF)—what we might call the cognitive signatures of minds under siege—are little known. We surveyed a gender‐balanced sample of 12‐ to 18‐year‐old Syrian refugees (n = 240) and Jordanian non‐refugees (n = 210) living in Jordan. We examined the relative contributions of poverty, trauma exposure, posttraumatic stress, and insecurity to variance in inhibitory control and working memory. We observed associations between poverty and WM, suggesting that, even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…A recent study on Yazidi children indicated that preschoolers, living in a critically adverse context, show lower scores in hot and cool EFs tasks, in particular in delay of gratification and inhibition abilities, with a specific effect on motor (circle drawing task) and prevalent response (day and night Stroop task) control (Pellizzoni et al, 2019), thus confirming previous developmental research (Merz et al, 2016). On the other hand, a study conducted by Chen et al (2019) underlines a specific effect of poverty, but not violence, on WM. These findings highlight the importance of carefully distinguishing between types of childhood adversity exposure (e.g., violence and poverty) in order to identify the specific relevant neurocognitive pathways underlying children's cognitive functioning as well as their psychosocial well-being.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…A recent study on Yazidi children indicated that preschoolers, living in a critically adverse context, show lower scores in hot and cool EFs tasks, in particular in delay of gratification and inhibition abilities, with a specific effect on motor (circle drawing task) and prevalent response (day and night Stroop task) control (Pellizzoni et al, 2019), thus confirming previous developmental research (Merz et al, 2016). On the other hand, a study conducted by Chen et al (2019) underlines a specific effect of poverty, but not violence, on WM. These findings highlight the importance of carefully distinguishing between types of childhood adversity exposure (e.g., violence and poverty) in order to identify the specific relevant neurocognitive pathways underlying children's cognitive functioning as well as their psychosocial well-being.…”
Section: Introductionsupporting
confidence: 70%
“…Furthermore, at a psychological level, differences in domain general cognitive abilities (e.g., intelligence), number words system used, and specific educational stimulations could have driven the data. Lastly, the level of poverty experienced in the specific geopolitical context may have had an impact on the differences we observed in preschool children involved in our study (see Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…One project focused on innovative methodologies to measure program impacts beyond self-reported data [ 30 ]. Panter-Brick and colleagues evaluated a brief psychosocial intervention delivered to Syrian refugee and Jordanian non-refugee adolescents, combining mental health self-reports [ 31 ], stress biomarkers [ 32 , 33 ], and tablet-based cognitive testing [ 34 ].…”
Section: R2hc-funded Mhpss Researchmentioning
confidence: 99%
“…Hair cortisol concentrations dropped by one-third, demonstrating a beneficial regulation of physiological stress [ 32 , 33 ]. However, no treatment effects were found for measures of cognitive function [ 34 ], or resilience [ 36 ], demonstrating that brief interventions can make notable impacts on psychosocial and biological stress, without necessarily changing broader social and developmental outcomes. These scientific findings informed programmatic decisions: Mercy Corps integrated elements of stress-attunement into its regional livelihood interventions and resilience-building efforts [ 30 ].…”
Section: Initial Findingsmentioning
confidence: 99%
“…Children outside high-income communities have widely varying experiences with different types of computer interfaces (keypads, keyboards, touchscreens). Chen et al (2019) found that local and refugee children in Jordan learned to complete tablet-based tasks with only a few minutes of introduction, relying on their familiarity with cell phones (over 80% reported having one at home) rather than personal computers. Tablet-based task administration may help bridge the gap between children with and without experience using a personal computer, with the added benefit of improving mobility for geographically remote sites.…”
Section: Generalizability Of Statistical Learningmentioning
confidence: 99%